2019
DOI: 10.1159/000500040
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review of Virtual Reality-Based Interventions to Promote Well-Being for People Living with Dementia and Mild Cognitive Impairment

Abstract: Assistive technology including virtual reality and augmented reality has gained interest as a novel intervention in a range of clinical settings. This technology has the potential to provide mental stimulation, a connection to autobiographical memory through reminiscence, and enhanced quality of life (QoL) to people living with dementia (PLWD) and mild cognitive impairment (MCI). In this mini-review, we examine the available evidence from studies reporting on the potential benefits of virtual and augmented rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(139 citation statements)
references
References 42 publications
5
133
0
1
Order By: Relevance
“…A literature review on potential bene ts of VR experience concluded that such experience may provide an opportunity to enjoy leisurely activities that may promote quality of life, psychological well-being, and social interaction in people with dementia without leaving their home [35]. They located nine studies of varying study designs and durations [35]. The common barriers in VR use across the studies were confusion (n=3), discomfort associated with headset (n=2), sadness (n=1), tiredness (n=1), and di culty with the technology (n=1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review on potential bene ts of VR experience concluded that such experience may provide an opportunity to enjoy leisurely activities that may promote quality of life, psychological well-being, and social interaction in people with dementia without leaving their home [35]. They located nine studies of varying study designs and durations [35]. The common barriers in VR use across the studies were confusion (n=3), discomfort associated with headset (n=2), sadness (n=1), tiredness (n=1), and di culty with the technology (n=1).…”
Section: Discussionmentioning
confidence: 99%
“…BroomX©) to generate realistic images, sounds and other sensations that simulate an user's physical presence in a virtual or imaginary environment [36]. The technology does not need a specialist/technical person to setup the machine, to use the VR program [35] and is cost effective for people with psychotic disorders [37]. A randomized control study in hospitalized patients (n=116) with psychotic disorders found that six months' VR experience improved participants' Quality-Adjusted Life Years (QALY) (effect size [ES]=0.01, 95% CI 0.03-0.07) [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various activities (e.g. listening to music, singing, dancing, reading, painting, drawing, cooking, knitting, talking, listening to others, playing with a pet, playing video games, and virtual reality [VR] experience) engaging individuals with mental stimulation, reminiscence, and orientation had been used as non-pharmacologic interventions in clinical setting [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…VR experience is considered a computer-generated non-pharmacologic intervention focusing on sensory stimulation using a virtual environment [35,36]. An individual using VR can look around or move around in an arti cial environment [36].…”
Section: Introductionmentioning
confidence: 99%